Moderni = The Moderns. - Exhibition. I Moderni = The Moderns. Castello di Rivoli Museo d'Arte Contemporanea Rivoli (Torino). 2003-04-16. 2003-08-24; Agamben, Giorgio; Ali, Mohammed; Balanchine, George; Basilico, Stefano; Bergson, Henri; Bonami, Francesco; Breton, André; Bush, Kate; Chiodi, Stefano; Christov-Bakargiev, Carolyn; Clark, T.J.; et al. (Milano : Skira editore Genève - Milano, 2003)
The exhibition I Moderni = The Moderns presents sculpture, installation, paintings, text, sound, video and film created by artists working round the world today.This is one of the first international exhibitions to highlight the ways in which these new artists are distancing themselves from much postmodernist practice that characterized the end of the last century. This book documents the exhibition and also provides a new and unique anthology of modernist texts chosen by the artists of our time.
Akakce, Haluk ; Albenda, Ricci ; Bartolini, Massimo ; Benassi, Elisabetta ; Dean, Tacita ; Friedman, Tom ; Gillick, Liam ; Herrera, Arturo ; Holloway, Evan ; Jungen, Brian ; Lambie, Jim ; Martin, Daria ; Mehretu, Julie ; Nguyen-Hatsushiba, Jun ; Pardo, Jorge ; Pfeiffer, Paul ; Philipsz, Susan ; Pilson, John ; Starling, Simon ; Sze, Sarah ; Uklanski, Piotr ; Webb, Gary
Soundtrack p. 233-236
biog., ind. tent., gr. tent., bibliog. p. 221-233
Engels
Italiaans
boek